Factors influencing sheep farmer attitudes towards breeding tools across Mediterranean breeds - Martín-Collado D.; Vouraki S.; Rubio A.; Serrano M.; Argyriadou A.; Tsartsianidou V.; Triantafyllidis A.; Arsenos G.; Díaz C. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
One of the key challenges for the success of sheep breeding programmes is to achieve a wide farmer engagement, which in many cases, especially in sheep breeds, is far from being fully reached. Understanding farmer attitudes and its driving factors give key insights for designing extension activities aiming to increase farmers’ uptake of breeding tools. However, farmer attitudes towards breeding tools have only been studied in very few occasions. Here we investigated the attitude of Spanish and Greek sheep farmers towards breeding tools and the main factors affecting it. A farmer survey that includes a scale to measure farmers’ attitudes was designed. The survey included additional information on farm and farmer profiles. Data were analysed using multivariate statistical methods. Two hundred fifteen farmers from Greece and Spain completed the survey. We found large heterogeneity in farmers´ attitudes not only across countries and breeds but also within them. Although there were farmers with a clear positive attitude towards genetic and genomic breeding (n=58) and farmers with a very positive attitude towards traditional selection (n=58), the majority had a balanced attitude towards genetic and genomic breeding and traditional phenotypic selection (n=82). In both counties, farmers of business-oriented intensive farms (contrary to family or family business farms) tended to have the highest positive attitude towards genetic and genomic breeding compared to traditional selection. This study indicates the need of tailoring extension programs to demonstrate farmers the usefulness of genetic and genomic breeding tools to improve animal performance.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)